2017
DOI: 10.7455/ijfs/6.2.2017.a8
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic, antioxidant and antimicrobial properties of red sweet pepper (Capsicum annuum L. var. Llanerón) extracts: In vitro study

Abstract: Alcoholic and aqueous extracts were obtained from red sweet pepper (Capsicum annuum L.) by different methodologies to evaluate their cytotoxic, antioxidant and antimicrobial properties. Alcoholic extracts (MFP, MSd, SFP, SDP, SSd) from fresh red sweet pepper (FP) and dry pulp (DP) and seed (Sd) were obtained by maceration (M) and Soxhlet (S) equipment using methanol as extraction solvent; whereas aqueous extracts (LFP, LSd) were obtained by decoction followed by lyophilization (L). Human tumoral cell lines fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In this study, the antioxidant capacity of all tested extracts was evaluated with reducing power and DPPH assays. The antiradical activity of flavonoids and phenolic compounds is mainly based on the redox properties of their hydroxy groups and the structural relationships (Raybaudi-Massilia et al, 2017). In the present study, all extracts were able to reduce the free radical DPPH.…”
Section: Total Polyphenol Content (Tpc) Total Flavonoid (Tfc) and Ant...supporting
confidence: 50%
See 1 more Smart Citation
“…In this study, the antioxidant capacity of all tested extracts was evaluated with reducing power and DPPH assays. The antiradical activity of flavonoids and phenolic compounds is mainly based on the redox properties of their hydroxy groups and the structural relationships (Raybaudi-Massilia et al, 2017). In the present study, all extracts were able to reduce the free radical DPPH.…”
Section: Total Polyphenol Content (Tpc) Total Flavonoid (Tfc) and Ant...supporting
confidence: 50%
“…Red pepper (Capsicum annuum L.) is a good source of phenolic compounds, and flavonoids which are antioxidant components, as well as has vitamins A and C contents. Antioxidants naturally present in vegetables and fruits are powerful substances and can play an important role in neutralizing and absorbing free radicals which cause damage the body cells (Raybaudi-Massilia et al, 2017;Borra et al, 2013). Phenolic compounds in plant sources are extracted by different solvents.…”
Section: Total Polyphenol Content (Tpc) Total Flavonoid (Tfc) and Ant...mentioning
confidence: 99%
“…In particular, the freshness of the pepper is an important quality attribute to consumers [10]. In addition, this vegetable is a good source of antioxidants, flavonoids, phenolic acids and carotenoids [13,14]. Green peppers are harvested before they ripen completely and, recently, the phenological stage and harvest date have been defined as two key factors that significantly influence their bioactive compounds content.…”
Section: Introductionmentioning
confidence: 99%
“…The highest antioxidant activity showed sample of grape pomace (Alibernet) and this sample was also the highest in content of polyphenols, followed by the sample of Cabernet and Red Traminer (Figure 4). The phytochemical compounds have demonstrated that they can decrease the risk of developing various chronic diseases due to their antioxidant and radicalscavenging activities (Raybaudi-Massilia et al, 2017) and in addition, plantderived ingredients possessing antioxidant and antimicrobial properties, have the advantage of being readily accepted by consumers, as they are considered natural compounds. Different studies observed the composition and properties of apple pomace, revealing that it is an interesting raw material due to its content in phytochemicals such polyphenols with antioxidant and antiviral activities (Madrera et al, 2017).…”
Section: Total Polyphenols and Antioxidant Activity Of Pomacementioning
confidence: 99%